A Comprehensive Analysis on Route Discovery and Maintenance Features of DSDV, AODV and IERF Ad-hoc Routing Protocols - Gundalwar, PR; Bhaskar Y, Kathane (International Journal of Computer Sciences and Engineering, 2025)
MANET is a momentary network of nodes without any aid of any infrastructure and network proprietor. Each node in MANET acts as a router or host and moves in dynamic trajectory region according to applied protocol. Recent research work in MANET rise to design various novel protocols based on fundamental protocols proposed by IETF. The route discovery and maintenance feature of MANET routing is essential for its proactive, reactive or hybrid behavior. In this paper, we analyzed comprehensively route discovery and maintenance of DSDV, AODV and IERF ad-hoc routing protocol along with their basic functionality. This will facilitate for finding motive to assessment of competitive MANET routing protocols on performance metrics such as PDR, delay, throughput etc. according to their phenomenal nature. The DSDV protocol is outperformed than AODV and IERF. The IERF protocol is observed superior to AODV due to its key features such as path accumulation, node reliability pair factor and node pruning .